Consumo de Alimento y selección Fenotípica en Cuyes en la etapa de reproductores en Hembras y Machos en el CEYPSA. - Herrera Castro, María José (2017)
The present investigation was carried out at the Technical University of Cotopaxi, Salache , of the Veterinary Medicine Career, where food consumption was determined in the stage of female guinea pigs and breeding males, having as objectives the identification, and grouping by contemporary groups and similar phenotypic characteristics of the animals. The identification of guinea pigs is a method that allows the collection of data and determine the requirement of nutrients necessary for the animals. We started by selecting the animals in relation to their phenotypic characteristics, obtaining: colorados with swirl, colorados without swirl, painted without swirl, painted with whirlpool, whites and bayes we do the areteo to the animals with their respective codification. The weighing of the food, supply, and consumption of the same, was determined by the residue to obtain the results of food consumption in dry matter. Analyzed the 4 research groups, category number 4 (painted with eddies) is obtained with the highest consumption Of food (dry matter), which gives us an average of 457.37 gr. Groups of females 3 and 4 in category 2 (439.4) gr and 1 (269.9) are taken into account the groups of males 2,3 and 4 in categories 2 (714.4) and 6 (552.7) Gr. Of the three rations of food supplied there is the highest consumption of kikuyo in the breeders. Animals with phenotypic characteristics defined as painted with swirls in males and females are the ones with the highest consumption of food.